IMPLEMENTASI â€œPICTURE DESCRIPTIONâ€ PADA APLIKASI MEDIA PEMBELAJARAN BAHASA INGGRIS - Rizki Amelia; Dodon T. Nugrahadi; Irwan Budiman (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2015)
The development of technology information in education has been growing fastly. Nowadays, English takes an important role in education and global communication in the world. On learning process, English is a foreign language subject that will tested in National Final Examination so it needs mastery and enough understanding in studying English. By optimizing the process of delivering learning materials with the use of TIK that include multimedia aspects are expected to give good influence in helping students to understand the learning material. This research study is aimed at: (1) designing english learning media application â€œPicture Descriptionâ€; (2) to find out the influence of using english learning media application â€œPicture Descriptionâ€. The research validators included three expert in english educattion, two expert in instructional multimedia, and twenty four students. The result shows: the difference between average of studentsâ€™ study result from experiment class by using (learning media application) 80,70 with average of studentsâ€™ study result from control class (conventional teaching) 72,83 shows that english learning media application â€œPicture Descriptionâ€ able to support English teaching and learning process. Keywords: Media Learning, Picture Description. Perkembangan teknologi informasi dalam bidang pendidikan sudah berkembang pesat. Saat ini, bahasa inggris memiliki peranan penting dalam dunia pendidikan dan komunikasi global di kehidupan dunia. Pada proses pembelajaran, bahasa inggris merupakan mata pelajaran bahasa asing yang diujikan pada saat Ujian Akhir Nasional (UAN) sehingga perlu penguasaan serta pemahaman yang cukup dalam mempelajari mata pelajaran bahasa inggris. Dengan mengoptimalisasi proses penyampaian materi pembelajaran dengan pemanfaatan TIK yang terdapat aspek-aspek multimedia diharapkan memberi pengaruh yang baik dalam membantu siswa memahami materi yang dipelajari. Penelitian ini bertujuan untuk membangun aplikasi media pembelajaran bahasa inggris â€œpicture descriptionâ€ dan untuk mengetahui pengaruh penerapan aplikasi media pembelajaran bahasa inggris â€œpicture descrioptionâ€. Validator dari penelitian ini adalah 3 orang ahli bidang studi bahasa inggris , 2 orang ahli multimedia pembelajaran dan 24 siswa. Berdasarkan hasil penelitian, menunjukkan bahwa adanya perbedaan rata-rata hasil belajar siswa dari kelas eksperimen 80,70 dengan rata-rata hasil belajar siswa kelas kontrol 72,83 yang menunjukkan aplikasi media pembelajaran bahasa inggris â€œPicture Descriptionâ€ mampu menunjang proses pembelajaran bahasa inggris. Kata Kunci : Media Pembelajaran, Picture Description.